QUO VADIS REGULASI PEREDARAN OBAT BEBAS DAN OBAT BEBAS TERBATAS PADA SARANA NON-FARMASI - Muhammad Hanif (Supremasi Hukum: Jurnal Penelitian Hukum, 2024)
The distribution of drugs, especially over-the-counter drugs and restricted over-the-counter drugs, currently seems not to be properly controlled as there is a discrepancy between regulations and techniques in monitoring the distribution of them on non-pharmaceutical facilities. In response to this, the Government made changes by issuing Law Number 17 of 2023 about Health replacing Law Number 36 of 2009. This research aims to confirm that with the publication of Law Number 17 of 2023 about Health, there are regulations that explicitly regulate the procedures for implementing pharmaceutical practice. The results of this research show that although it is not perfect, the government has fulfilled its obligation to protect the public in terms of drug distribution.